Características de la terapia utilizada por los pobladores del centro poblado de Moche para el tratamiento de las enfermedades diarreicas agudas en niños de 1 a 10 años de edad enero-febrero 2014 - Martinez Marcelo, Pedro Dominique (2014)
This research work has as its objective to determine the characteristics of the therapy used by the inhabitants of the village of Moche center for the treatment of acute diarrheal diseases (ADDs) in children 1 to 10 years, to this end, it was applied as a technical survey data collection using a previously validated questionnaire and the following results were obtained; Of the population being surveyed it was found that 72% opted for the use of drugs for which 83% went to a health center, 15% went to the pharmacist and 2% automedico; 23% of respondents chose the consumption of medicinal plants and the remaining 5% natural products. With regard to pharmacological therapy, it was found that 83% used antibiotics and 17% oral rehydration salts, the most commonly used antibiotics were Bactrim with a 76 %, being the major use in the form of oral suspension, the next in use was the Furazolidone with 12% of the total followed by ciprofloxacin and Amikacin (Amikin) with 10% and 2% respectively. On the part of the traditional therapy, the most commonly used medicinal plants were sheets of matico with 26 %, with 12% manzanilla (flowers and the whole plant) and tea loaded, and to a lesser percentage the fruit of quince, among others. In regard to the use of natural products in the diarrheic symptoms 67% of the mothers (or guardians) were of the opinion that they do not have any benefit for diarrhea in children and 33% believe that it can be beneficial but not used